Investigations on biofilm forming bacteria involved in biocorrosion of carbon steel immerged in real wastewaters. (May 2020) - El-Bassi, Leila; Ziadi, Islem; Belgacem, Sabrine; Bousselmi, Latifa; Akrout, Hanene
Abstract: Bacteria are able to construct biofilm adjacent to carbon steel surface and leading to the biocorrosion and metal deterioration. The impact of wasterwaters' indigenious bacteria on biocorrosion of carbon steel was evaluated under different pH values (3, 7 and 9), two chloride concentrations (0.5 g/L and 1.5 g/L), and for two wastewaters. In tannery wastewaters (TWW) and under pH 3, Pseudomonas aeruginosa sp . (MN788665) and Enterobacter aerogenes sp . (MN788688) were able to establish an irreversible adhesion on the first stage of biofilm formation on the carbon steel surface due to hydrophobic behaviour of the bacteria. However, under the same pH, bacteria from industrial wastewaters (IWW) such us Brevundimonas diminuta sp . (MN788672) and Enterobacter aerogenes sp . (MN788689) promote the reversible adhesion followed by a continuous attachment and consequently a limited biofilm. Subsequently, in TWW and 0.5 g/L of chlorides, indigenious bacteria like Enterobacter aerogenes sp. (MN790737 ) and Raoultella ornithinolytica sp. promote an irreversible attachment of biofilm enhanced by their hydrophobic property contrarily to the bacteria isolated in the medium at chloride concentration of 1.5 g/L. In IWW, 1.5 g/L of chlorides the biofilm attachment is reversible and therefore its inhibition role is of little influence. Highlights: Hydrophobic bacteria like; Pseudomonas sp . and Enterobacter sp . enhances an irreversible adhesion of biofilm at pH 3. Hydrophilic bacteria like ; Brevundimonas sp . and Enterobacter sp . promote a reversible adhesion at pH 3. Under 0.5g/L of chlorides concentrations, bacteria like Enterobacter sp . (MN790737 ) and Raoultella sp . promote an irreversible attachment of biofilm.